2005
DOI: 10.4049/jimmunol.175.4.2510
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii Can Ablate Vaccine-Induced Long-Term Protection in Mice

Abstract: Malaria is a serious cause of morbidity and mortality for people living in endemic areas, but unlike many other infections, individuals exposed to the parasite do not rapidly become resistant to subsequent infections. High titers of Ab against the 19-kDa C-terminal fragment of the merozoite surface protein-1 can mediate complete protection in model systems; however, previous studies had not determined whether this vaccine generated long-term protection. In this study, we report that functional memory cells gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 45 publications
8
125
1
Order By: Relevance
“…In this study, we showed that mBC levels increased significantly postimmunization at the time points assessed and that these responses correlated with longer-term serum IgG levels, similar to that seen with the AMA1 protein vaccine in a phase Ia clinical trial (63). Although the direct role for these cells in immediate and long-term immunity to malaria remains unclear (27,28,67), their evaluation in blood-stage malaria vaccine clinical trials is becoming more routine (63,68,69). Such studies should shed more light on the role that these cells play in the maintenance and boostability of vaccine-induced IgG responses and how these cells are modulated by chronic malaria infection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study, we showed that mBC levels increased significantly postimmunization at the time points assessed and that these responses correlated with longer-term serum IgG levels, similar to that seen with the AMA1 protein vaccine in a phase Ia clinical trial (63). Although the direct role for these cells in immediate and long-term immunity to malaria remains unclear (27,28,67), their evaluation in blood-stage malaria vaccine clinical trials is becoming more routine (63,68,69). Such studies should shed more light on the role that these cells play in the maintenance and boostability of vaccine-induced IgG responses and how these cells are modulated by chronic malaria infection.…”
Section: Discussionmentioning
confidence: 71%
“…Studies of naturally acquired immunity and experimental immunization in humans and animal models have painted a complex picture (14), with protection associated with Abs against merozoite Ags (15), specific IgG isotypes (16), T cells against blood-stage parasites (17)(18)(19)(20), innate effector cell types (21)(22)(23), serum cytokines (21,24), and regulatory T cells (25). Numerous other studies described the immunomodulatory effects of parasite exposure on T and B lymphocyte populations (26)(27)(28). It is perhaps not surprising that single-modality vaccine platforms, aiming to induce a single type of immune response, have failed to impact on the blood-stage growth rates of P. falciparum in clinical trials.…”
mentioning
confidence: 99%
“…iRBCs have been shown to cause apoptosis of B cells, T cells, macrophages, and endothelial cells in human in vitro studies and in animal malaria models (10,15,16,33,48,55,56), and a recent study found that the majority of CD8 ϩ splenic DCs harvested from Plasmodium chabaudi-infected mice were apoptotic (45). Apoptosis of DC subsets could interfere with developing antimalarial immune responses, and further studies are required to establish the physiological relevance of our observation and elucidate the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Kinyanjui et al (38) showed that IgG responses in Kenyan children following (41) showed that human B cell memory and long-lived Ab levels expand gradually with repeated infections. In mice, although some studies have shown normal development of memory B cell responses during Plasmodium infection (22,42), others have shown defects in memory B cell generation or maintenance (43,44). Crompton and colleagues (45) also have suggested that P. falciparum drives short-lived plasma cell responses, which may explain why Ab levels are not maintained in the absence of repeated exposures, and because memory B cell and plasma cell responses are regulated independently of each other, the presence of memory B cells may not be required to maintain serum Ab levels.…”
Section: Discussionmentioning
confidence: 99%